Callus induction and regeneration of date palm (Phoenix dactylifera L.) cv. Zambli through somatic embryogenesis from four layers of young leaves explant - Masna Maya Sinta; Rizka Tamania Saptari; Imron Riyadi; Sumaryono Sumaryono (Menara Perkebunan, 2024)
The Zambli variety of date palm shows potential for cultivation in tropical regions, as its fruits are edible during the Rutab stage. However, large-scale production of Zambli seedlings presents a significant challenge. In vitro propagation offers a solution for producing large quantities of clonal planting material. This study focuses on inducing callus formation from the four-layered shoot tips of young leaves and regenerating these calli into plantlets through somatic embryogenesis. Explants were cultured on a modified MS medium with 10, 50, or 100 mg L-1 2,4-dichlorophenoxyacetic acid (2,4-D), combined with 1 or 3 mg L-1 N6-(2-isopentenyl)adenine (2-iP). Embryo maturation was performed on the same medium without 2,4-D, while a hormone-free medium was used for plantlet regeneration. The results indicated that the highest callus induction occurred from the younger leaf layer (layer 1) in the medium containing 100 mg L-1 2,4-D and 1 mg L-1 2-iP, achieving a callus formation rate of 82.3%. Successful callus induction was achieved from the first, second, and third layers of young leaves. Somatic embryo maturation and plantlet regeneration were also completed, producing vigorous, well-rooted plantlets. Additionally, the development of date palm cv. Zambli in vitro culture through somatic embryogenesis was confirmed through histological analysis.